Disrupted Protein Expression and Altered Proteolytic Events in Hypophosphatemic Dentin Can Be Rescued by Dentin Matrix Protein 1 - Guirado, Elizabeth; Chen, Yinghua; Ross, Ryan D.; Zhang, Youbin; Chaussain, Catherine; George, Anne (Frontiers in Physiology, 2020)
Dentin, one of the four mineralized tissues of the craniofacial complex, forms sequentially from the deposition of an organic matrix to the nucleation of an inorganic phase within the matrix scaffold. Several promoters and inhibitors of mineralization support and regulate mineral nucleation. Clinical and experimental evidence suggest that dentin matrix protein 1 (DMP1) and phosphate-regulating neutral endopeptidase (PHEX) cooperate and are necessary for the formation of a cohesive dentin layer. The following study investigates the effect of PHEX loss-of-function on dentin matrix formation preceding mineralization. Using the Hyp mouse, an animal model for X-linked hypophosphatemia (XLH), we identified an irregular distribution of dentin extracellular matrix proteins. Likewise, dental pulp stem cells (DPSCs) from XLH patients exhibited altered proteolytic events with disrupted extracellular matrix deposition. Further differentiation assays demonstrated that XLH DPSCs exhibited impaired matrix mineralization. Overexpression of DMP1 in XLH DPSCs restored the irregular protein processing patterns to near-physiological levels. Our results support the hypothesis that hypophosphatemia resulting from PHEX loss-of-function affects the integrity of the organization of the dentin matrix and suggests that exogenous DMP1 can restore physiological processing of matrix proteins, in addition to its canonical role in mineralization.